Patel : political ideas and policies - Sinha, Shakti; Roy, Himanshu (SAGE Publications India Pvt Ltd ; SAGE Publications Inc, 2019)
"Patel: Political Ideas and Policies comprehensively presents the different facets of Sardar Patel's political life, his ideas and their applications. The book provides a detailed analysis of his perspectives on liberal democracy, nationalism and the state--the three pillars of his political life. Patel's role in the Constituent Assembly, transfer of power, integration of princely states with independent India and their territorial reorganization, administrative reforms, formation of the Planning Commission and creation of India's foreign policy were decisive to the consolidation and the very survival of India as a nation. He played an equally decisive role in the formulation of India's economic policies. After Patel's death in 1950, his contributions to the nation have often been undermined and various negative characteristics have been attributed to him. This book aims to debunk these notions. It is based on the collected works of Patel and attempts to fill in the gap created by the absence of any significant academic work on his life and work."--Provided by publisher